Effect of 6-paradol Nanoparticle on Some Testis and Epididymis Parameters in Diabetic Rats Induced by Streptozotocin - Abdullah, Jasim A.; Al-Mayali, Hussein K.; Al Naeely, Ahmed J. H. (Scientific Journal of Medical Research, 2021)
Objective: This study to investigate the role of 6-paradol nanoparticle in the treatment the of the changes occurs in the testis and epididymis and some semen parameters in male rats which induced by streptozotocin. Methods: Different concentrations 20 mg and 40 mg/kg of 6-paradol nanoparticle used as treatment through 60 days in some physiological and histological criteria in seven groups diabetic rats Rattus norvegicus induced by streptozotocin and the parameters that studied were concentration of sperms, motility, percentage of sperms abnormalities, percentage of sperms viability. number of the sperm cell, Sertoli and ledige, diameters and thickness of seminiferous tubules. Results: the results showed a significant decrease in Concentration of sperms, motility, Percentage of sperms viability, number of the sperm cell, Sertoli and leydige, diameters and thickness of seminiferous tubules in male rats (G3) 60 mg which was given streptozotocin to induce diabetes and showed a significant increase in percentage of sperms abnormalities, while in (G4, G5) 20 mg, 40 mg which was treated by 6-paradol nanoparticle showed a significant increase in Concentration of sperms, motility, Percentage of sperms viability, number of sperm cell, Sertoli and ledige, diameters and thickness of seminiferous tubules and showed a significant decrease in the percentage of sperms abnormalities. Conclusion: We can consider the 6-paradol is a very good substance because of the efficiency in the treatment of the testis and epididymis and useful as an antibiotic or antioxidant because it is very safe on the body and also tiny size in the nanometres even easily enters to the cell and gives good result.